2009
DOI: 10.1002/aic.12073
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of ethanol and acetic acid from methane and carbon dioxide with a continuous, stepwise reactor

Abstract: in Wiley InterScience (www.interscience.wiley.com).The synthesis of C 2 -oxygenates such as ethanol and acetic acid accomplished by CH 4 dissociation and subsequent CO 2 insertion onto methyl radicals, named the stepwise reaction technology, has been demonstrated to be both feasible and efficient through initial experiments conducted in microreactor units. This article describes the development of this technology, highlighting the aforementioned stepwise technology using a dual-reactor system, which can ensure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 8 publications
0
21
1
Order By: Relevance
“…1,2 Numerous supported catalysts based on group VIII (noble metals) based supported catalysts have been tested for CO 2 methanation. [3][4][5][6][7] Notably, Ni catalysts supported on oxide supports were most widely applied attributed to their higher activity and selectivity. [8][9][10] Support affects catalytic properties by manipulating the interaction between the active phase and support, thereby improving the attraction capacity of catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Numerous supported catalysts based on group VIII (noble metals) based supported catalysts have been tested for CO 2 methanation. [3][4][5][6][7] Notably, Ni catalysts supported on oxide supports were most widely applied attributed to their higher activity and selectivity. [8][9][10] Support affects catalytic properties by manipulating the interaction between the active phase and support, thereby improving the attraction capacity of catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The diagram of the reaction apparatus is shown in Fig. 4 and was the same as the reaction apparatus of our previous paper on acetic acid synthesis from CH 4 and CO 2 12 . There was 1.5 g of catalysts used in reactor A and B, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…C 2 -oxygenate synthesis from CH 4 and CO 2 is thermodynamically unfavourable at low temperatures, but this can be overcome through a stepwise reaction technology that has been proposed by our group 11 . In this process, *CH 4 is first adsorbed on the catalyst surface (M) and then dissociated to generate CH x -M; subsequently, the *CO 2 species is inserted into the C-M bond to form *CH x COO before finally forming acetic acid from *CH x COO hydrogenation 12 13 14 . It was found that the Pd-Co and Cu-Co bi-metal supported on TiO 2 catalysts exhibited good activity for acetic acid from CH 4 and CO 2 15 .…”
mentioning
confidence: 99%
“…Wilcox investigated the direct synthesis of acetic acid by Pd/C and Pd/Al 2 O 3 catalysts (Wilcox et al, 2003), while obtained the low conversion of methane as CO 2 had lower free energy and showed the strong chemical inertness, resulting in the thermodynamic factors limiting the acetic acid yield in chemical balance. However, in order to improve the conversion of CH 4 , designing an appropriate reactor (Huang et al, 2010) and two catalytic system coupling reaction (Spivery et al, 2008) were also proposed.…”
Section: Oxygen-adding Oxidationmentioning
confidence: 99%